Mobile path loss prediction model for forest areas using MIMO fuzzy logic system - Phaiboon, Supachai; Phokharatkul, Pisit; Kittitummawong, Piti; Somkuarnpanit, Suripon (My University, 2006)
This paper proposes a method to predic mobile path loss in forests using MIMO fuzzy logic system. The multi-input was classified into seven input parameters defined as, X1 is number of trees/m2 and X2 to X7 are tree structure parameters. These crisp inputs are classified by fuzzifier to fuzzy sets and then inferenced using fuzzy linguistic rule base into multi - output path loss slopes via de-fuzzifier. For this study, we classified the terrains into high-, medium-, low- density and grass area and used the simple linguistic rules for prediction the path loss slopes. We performed measurements in different forest densities at a frequency of 1.8 GHz with base station antenna height in a range of 3, 4, and 5 m above ground while the receiving antenna height was fixed at 1.8 m above ground. The results have shown that fuzzy logic approach provides more accurate prediction of path loss slopes than that of conventional empirical mathematic model. The proposed models will be useful for the local wireless network and micro-cell design of mobile communication systems in forests.
Keywords: Forests; Low base station; MIMO fuzzy system; Mobile path loss slope